# |
ODE |
Mathematica |
Maple |
\[
{}\sin \left (x +y\right )-y y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime } y^{2}+3 x^{2} y = \sin \left (x \right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+x^{2} y^{\prime }+4 y = y^{3}
\] |
✗ |
✗ |
|
\[
{}y y^{\prime \prime \prime }+6 y^{\prime \prime }+3 y^{\prime } = y
\] |
✗ |
✗ |
|
\[
{}x^{3} y^{\prime \prime \prime }-4 y^{\prime \prime }+10 y^{\prime }-12 y = 0
\] |
✗ |
✗ |
|
\[
{}[x^{\prime }\left (t \right ) = x \left (t \right ) y \left (t \right )-6 y \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )-y \left (t \right )-5]
\] |
✗ |
✗ |
|
\[
{}x {y^{\prime \prime }}^{2}+2 y = 2 x
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }+2 \sin \left (x\right ) = \sin \left (2 t \right )
\] |
✗ |
✗ |
|
\[
{}4 x \left (x^{2}+y^{2}\right )-5 y+4 y \left (x^{2}+y^{2}-5 x \right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime }+t^{2} = \frac {1}{y^{2}}
\] |
✗ |
✗ |
|
\[
{}1-y^{2} \cos \left (t y\right )+\left (t y \cos \left (t y\right )+\sin \left (t y\right )\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}{\mathrm e}^{y}-2 t y+\left (t \,{\mathrm e}^{y}-t^{2}\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}\frac {1}{t^{2}+1}-y^{2}-2 t y y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}\frac {2 t}{t^{2}+1}+y+\left ({\mathrm e}^{y}+t \right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+b \left (t \right ) y^{\prime }+c \left (t \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+b \left (t \right ) y^{\prime }+c \left (t \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}x \left (1+x \right ) y^{\prime \prime }+\frac {y^{\prime }}{x^{2}}+5 y = 0
\] |
✓ |
✗ |
|
\[
{}y^{\prime } = \sin \left (y\right )-\cos \left (x \right )
\] |
✗ |
✗ |
|
\[
{}x^{3} y^{\prime }-\sin \left (y\right ) = 1
\] |
✗ |
✗ |
|
\[
{}y^{\prime }-\tan \left (y\right ) = \frac {{\mathrm e}^{x}}{\cos \left (y\right )}
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime \prime } = \sqrt {1-{y^{\prime \prime }}^{2}}
\] |
✓ |
✗ |
|
\[
{}y^{3} y^{\prime \prime } = -1
\] |
✓ |
✗ |
|
\[
{}x^{\prime \prime }-2 {x^{\prime }}^{2}+x^{\prime }-2 x = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }+{\mathrm e}^{-x^{\prime }}-x = 0
\] |
✗ |
✗ |
|
\[
{}x^{\prime \prime }-x^{\prime }+x-x^{2} = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}\left [x^{\prime }\left (t \right ) = \cos \left (x \left (t \right )\right )^{2} \cos \left (y \left (t \right )\right )^{2}+\sin \left (x \left (t \right )\right )^{2} \cos \left (y \left (t \right )\right )^{2}, y^{\prime }\left (t \right ) = -\frac {\sin \left (2 x \left (t \right )\right ) \sin \left (2 y \left (t \right )\right )}{2}\right ]
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = \sqrt {1-t^{2}-y^{2}}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = \frac {\ln \left (t y\right )}{1-t^{2}+y^{2}}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = \left (t^{2}+y^{2}\right )^{{3}/{2}}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = -\frac {4 t}{y}
\] |
✓ |
✗ |
|
\[
{}y^{\prime } = \frac {t^{2}}{y \left (t^{3}+1\right )}
\] |
✓ |
✗ |
|
\[
{}{\mathrm e}^{x} \sin \left (y\right )+3 y-\left (3 x -{\mathrm e}^{x} \sin \left (y\right )\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}\frac {4 x^{3}}{y^{2}}+\frac {12}{y}+3 \left (\frac {x}{y^{2}}+4 y\right ) y^{\prime } = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime } = \frac {x +y}{x -y}
\] |
✓ |
✗ |
|
\[
{}[x^{\prime }\left (t \right ) = 2-y \left (t \right ), y^{\prime }\left (t \right ) = y \left (t \right )-x \left (t \right )^{2}]
\] |
✗ |
✗ |
|
\[
{}\left [x^{\prime }\left (t \right ) = x \left (t \right )-x \left (t \right )^{2}-x \left (t \right ) y \left (t \right ), y^{\prime }\left (t \right ) = \frac {y \left (t \right )}{2}-\frac {y \left (t \right )^{2}}{4}-\frac {3 x \left (t \right ) y \left (t \right )}{4}\right ]
\] |
✗ |
✗ |
|
\[
{}[x^{\prime }\left (t \right ) = -\left (x \left (t \right )-y \left (t \right )\right ) \left (1-x \left (t \right )-y \left (t \right )\right ), y^{\prime }\left (t \right ) = x \left (t \right ) \left (2+y \left (t \right )\right )]
\] |
✗ |
✗ |
|
\[
{}[x^{\prime }\left (t \right ) = y \left (t \right ) \left (2-x \left (t \right )-y \left (t \right )\right ), y^{\prime }\left (t \right ) = -x \left (t \right )-y \left (t \right )-2 x \left (t \right ) y \left (t \right )]
\] |
✗ |
✗ |
|
\[
{}[x^{\prime }\left (t \right ) = \left (2+x \left (t \right )\right ) \left (y \left (t \right )-x \left (t \right )\right ), y^{\prime }\left (t \right ) = y \left (t \right )-x \left (t \right )^{2}-y \left (t \right )^{2}]
\] |
✗ |
✗ |
|
\[
{}\left [x^{\prime }\left (t \right ) = y \left (t \right ), y^{\prime }\left (t \right ) = x \left (t \right )-\frac {x \left (t \right )^{3}}{5}-\frac {y \left (t \right )}{5}\right ]
\] |
✗ |
✗ |
|
\[
{}\left [x^{\prime }\left (t \right ) = x \left (t \right ) \left (1-x \left (t \right )-y \left (t \right )\right ), y^{\prime }\left (t \right ) = y \left (t \right ) \left (\frac {3}{4}-y \left (t \right )-\frac {x \left (t \right )}{2}\right )\right ]
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y+y^{3} = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+\mu \left (1-y^{2}\right ) y^{\prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+\cos \left (t \right ) y^{\prime }+3 y \ln \left (t \right ) = 0
\] |
✗ |
✗ |
|
\[
{}\left (x +3\right ) y^{\prime \prime }+x y^{\prime }+\ln \left (x \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}\left (x -2\right ) y^{\prime \prime }+y^{\prime }+\left (x -2\right ) \tan \left (x \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }-\frac {t}{y} = \frac {1}{\pi }
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime }+y+\frac {y^{3}}{5} = \cos \left (w t \right )
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{5}+y+\frac {y^{3}}{5} = \cos \left (w t \right )
\] |
✗ |
✗ |
|
\[
{}t y^{\prime \prime \prime }+\sin \left (t \right ) y^{\prime \prime }+8 y = \cos \left (t \right )
\] |
✗ |
✗ |
|
\[
{}t \left (t -1\right ) y^{\prime \prime \prime \prime }+{\mathrm e}^{t} y^{\prime \prime }+4 t^{2} y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime \prime }+t y^{\prime \prime }+t^{2} y^{\prime }+t^{2} y = \ln \left (t \right )
\] |
✗ |
✗ |
|
\[
{}\left (x -4\right ) y^{\prime \prime \prime \prime }+\left (1+x \right ) y^{\prime \prime }+\tan \left (x \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}\left (x^{2}-2\right ) y^{\left (6\right )}+x^{2} y^{\prime \prime }+3 y = 0
\] |
✗ |
✗ |
|
\[
{}t y^{\prime \prime \prime }+\sin \left (t \right ) y^{\prime \prime }+4 y = \cos \left (t \right )
\] |
✗ |
✗ |
|
\[
{}t \left (t -1\right ) y^{\prime \prime \prime \prime }+{\mathrm e}^{t} y^{\prime \prime }+7 t^{2} y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime \prime }+t y^{\prime \prime }+5 t^{2} y^{\prime }+2 t^{3} y = \ln \left (t \right )
\] |
✗ |
✗ |
|
\[
{}\left (x -1\right ) y^{\prime \prime \prime \prime }+\left (x +5\right ) y^{\prime \prime }+\tan \left (x \right ) y = 0
\] |
✗ |
✗ |
|
\[
{}\left (x^{2}-25\right ) y^{\left (6\right )}+x^{2} y^{\prime \prime }+5 y = 0
\] |
✗ |
✗ |
|
\[
{}y = {y^{\prime }}^{2}-x y^{\prime }+\frac {x^{3}}{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime } y^{\prime \prime }-x^{2} y y^{\prime }-x y^{2} = 0
\] |
✗ |
✗ |
|
\[
{}x \left (x^{2} y^{\prime }+2 x y\right ) y^{\prime \prime }+4 x {y^{\prime }}^{2}+8 x y y^{\prime }+4 y^{2}-1 = 0
\] |
✗ |
✗ |
|
\[
{}a^{2} y^{\prime \prime } = 2 x \sqrt {1+{y^{\prime }}^{2}}
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime } = y^{2}+x
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+y^{2} = 0
\] |
✗ |
✗ |
|
\[
{}\sin \left (x \right ) \tan \left (y\right )+1+\cos \left (x \right ) \sec \left (y\right )^{2} y^{\prime } = 0
\] |
✓ |
✗ |
|
\[
{}\left (x \,{\mathrm e}^{y}+y-x^{2}\right ) y^{\prime \prime } = 2 x y-{\mathrm e}^{y}-x
\] |
✗ |
✗ |
|
\[
{}x^{2} y^{\prime } = y
\] |
✓ |
✗ |
|
\[
{}x^{3} \left (x -1\right ) y^{\prime \prime }-2 \left (x -1\right ) y^{\prime }+3 x y = 0
\] |
✓ |
✗ |
|
\[
{}x^{2} y^{\prime \prime }+\left (2-x \right ) y^{\prime } = 0
\] |
✓ |
✗ |
|
\[
{}x^{4} y^{\prime \prime }+y \sin \left (x \right ) = 0
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{x^{2}}-\frac {y}{x^{3}} = 0
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime }+\frac {n y^{\prime }}{x^{2}}+\frac {q y}{x^{3}} = 0
\] |
✓ |
✗ |
|
\[
{}x^{2} y^{\prime \prime }+x y^{\prime }+\left (-n^{2}+x^{2}\right ) y = 0
\] |
✓ |
✗ |
|
\[
{}x^{\prime \prime }+\left (5 x^{4}-9 x^{2}\right ) x^{\prime }+x^{5} = 0
\] |
✗ |
✗ |
|
\[
{}v^{\prime \prime } = \left (\frac {1}{v}+{v^{\prime }}^{4}\right )^{{1}/{3}}
\] |
✗ |
✗ |
|
\[
{}\sqrt {y^{\prime }+y} = \left (y^{\prime \prime }+2 x \right )^{{1}/{4}}
\] |
✗ |
✗ |
|
\[
{}4 y {y^{\prime }}^{3}-2 x^{2} {y^{\prime }}^{2}+4 x y y^{\prime }+x^{3} = 16 y^{2}
\] |
✓ |
✗ |
|
\[
{}y^{\prime \prime \prime } y^{\prime }-3 {y^{\prime \prime }}^{2}+3 y^{\prime \prime } {y^{\prime }}^{2}-2 {y^{\prime }}^{4}-x {y^{\prime }}^{5} = 0
\] |
✗ |
✗ |
|
\[
{}\left (1+y^{2}\right ) y^{\prime \prime }-2 y {y^{\prime }}^{2}-2 \left (1+y^{2}\right ) y^{\prime } = y^{2} \left (1+y^{2}\right )
\] |
✗ |
✗ |
|
\[
{}\left (x y^{\prime }-y\right )^{2} = a \left (1+{y^{\prime }}^{2}\right ) \left (x^{2}+y^{2}\right )^{{3}/{2}}
\] |
✓ |
✗ |
|
\[
{}\left (x y^{\prime }-y\right ) \left (y y^{\prime }+x \right ) = h^{2} y^{\prime }
\] |
✓ |
✗ |
|
\[
{}\left (x y^{\prime }-y\right ) \left (x -y y^{\prime }\right ) = 2 y^{\prime }
\] |
✓ |
✗ |
|
\[
{}y^{\prime } y^{\prime \prime }-x^{2} y y^{\prime } = x y^{2}
\] |
✗ |
✗ |
|
\[
{}x^{4} y^{\prime \prime }+x y^{\prime }+y = \frac {1}{x}
\] |
✓ |
✗ |
|
\[
{}\left (y^{2}+2 x^{2} y^{\prime }\right ) y^{\prime \prime }+2 \left (x +y\right ) {y^{\prime }}^{2}+x y^{\prime }+y = 0
\] |
✗ |
✗ |
|
\[
{}\left (x^{3}+x +1\right ) y^{\prime \prime \prime }+\left (3+6 x \right ) y^{\prime \prime }+6 y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime \prime }+\frac {y^{\prime }}{x^{{1}/{3}}}+\left (\frac {1}{4 x^{{2}/{3}}}-\frac {1}{6 x^{{1}/{3}}}-\frac {6}{x^{2}}\right ) y = 0
\] |
✗ |
✗ |
|
\[
{}y^{\prime }+\frac {\tan \left (y\right )}{x} = \frac {\tan \left (y\right ) \sin \left (y\right )}{x^{2}}
\] |
✓ |
✗ |
|
\[
{}y^{\prime }+\frac {y \ln \left (y\right )}{x} = \frac {y}{x^{2}}-\ln \left (y\right )^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime }+\frac {\tan \left (y\right )}{x} = \frac {\tan \left (y\right ) \sin \left (y\right )}{x^{2}}
\] |
✓ |
✗ |
|
\[
{}\sec \left (y\right )^{2} y^{\prime }+2 x \tan \left (y\right ) = x^{3}
\] |
✓ |
✗ |
|
\[
{}\left (x y^{\prime }-y\right )^{2} = a \left (1+{y^{\prime }}^{2}\right ) \left (x^{2}+y^{2}\right )^{{3}/{2}}
\] |
✓ |
✗ |
|
\[
{}\left (a {y^{\prime }}^{2}-b \right ) x y+\left (b \,x^{2}-y^{2} a +c \right ) y^{\prime } = 0
\] |
✓ |
✗ |
|
\[
{}a x y {y^{\prime }}^{2}+\left (x^{2}-y^{2} a -b \right ) y^{\prime }-x y = 0
\] |
✓ |
✗ |
|
\[
{}y {y^{\prime }}^{2} x +\left (x^{2}+y^{2}-h^{2}\right ) y^{\prime }-x y = 0
\] |
✗ |
✗ |
|
\[
{}\left (x^{2} y^{\prime }+y^{2}\right ) \left (x y^{\prime }+y\right ) = \left (y^{\prime }+1\right )^{2}
\] |
✗ |
✗ |
|
\[
{}\left (x y^{\prime }-y\right ) \left (x -y y^{\prime }\right ) = 2 y^{\prime }
\] |
✓ |
✗ |
|
\[
{}x^{5} y^{\left (6\right )}+x^{4} y^{\left (5\right )}+x y^{\prime }+y = \ln \left (x \right )
\] |
✗ |
✗ |
|